Solubility determination, model evaluation, Hansen solubility parameter and thermodynamic properties of benflumetol in pure alcohol and ester solvents. (March 2021) - Sha, Jiao; Yang, Xiaoqing; Hu, Xiaoran; Huang, Zibo; Cao, Zidan; Wan, Yameng; Sun, Renren; Jiang, Gaoliang; He, Haixia; Li, Yu; Li, Tao; Ren, Baozeng
Highlights: Solubility of benflumetol in pure alcohols and esters was measured. Hansen solubility parameter was applied to analyze the solubility behavior. KAT-LSER model was applied to analyze the solvent effect. Solubility was fitted by λh, modified Apleblat, Two-Suffix Margules, NRTL and UNIQUAC models. Thermodynamic properties of the solution were calculated. Abstract: The equilibrium solubility and thermodynamic properties of benflumetol in methanol, ethanol, n-propanol, n-butanol, n-pentanol, n-hexanol, n-heptanol, n-octanol, methyl acetate, ethyl acetate, n-propyl acetate, n-butyl acetate and n-pentyl acetate were reported. Solubility determinations were performed through the laser monitoring method at T = (278.15–323.15) K and p = 101.3 kPa. It is found that the mole fraction solubility of benflumetol increases apparently with the augmented experimental temperature. In addition, the solubility of benflumetol in all ester solvents is greater than that in alcohol solvents. The maximum mole fraction solubility of benflumetol is obtained in n-pentyl acetate (4.061 × 10 −2, T = 323.15 K), and the minimum mole fraction solubility of benflumetol is obtained in methanol (1.341 × 10 −5, T = 278.15 K). The Hansen solubility parameter for benflumetol as well as selected solvents was summarized to analyse the probabilities of miscibility between solute and solvents. The analysis consequence shows that the miscibility of benflumetol with selected solvents is caused by a combination of factors. All recorded solubility of benflumetol were regressed by λh model, modified Apleblat model, two-Suffix Margules model, NRTL model and UNIQUAC model. By comparison, it can be found that the average ARD and 10 4 RMSD of the modified Apelblat model and NRTL model are smaller than the other three models, indicating that these two moedls are more suitable for correlating the solubility data. In addition, the apparent thermodynamic properties of benflumetol in all neat solvents were calculated and investigated by the Van't Hoff equation. The results illustrated that the dissolution process of benflumetol is an entropy-driven endothermic process.